Musawwighāt al-Mubtada’ bi al-Nakirah: Their Types and Functions in the Book Awa’iq Ath-Thalab by Sheikh Abdus Salam bin Barjas (A Syntactic Analysis) - Muhammad Haritsah Rais; Akmaliyah Akmaliyah; Maman Abdul Djaliel; Setia Gumilar (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2026)
In Arabic grammar, the mubtada’ is generally required to be an isim ma‘rifah. However, Arabic texts frequently employ isim nakirah as the mubtada’, raising questions about the linguistic factors that permit its use. This study aims to identify the types and functions of musawwighāt al-mubtada’ bi an-nakirah in Awa’iq Ath-Thalab by Shaykh Abdus Salam bin Barjas based on Ibn Hisyām al-Anṣārī’s theory in Mughnī al-Labīb. This study employs a qualitative approach using the library research method. Data were collected through reading and note-taking by identifying sentences containing musawwighāt al-mubtada’ bi an-nakirah and analyzing them according to Ibn Hisyām al-Anṣārī’s framework. The findings reveal four types of musawwighāt al-mubtada’ bi an-nakirah: the general nakirah, the qualified nakirah, the nakirah whose predicate is a zharf, jar-majrūr, or jumlah, and the governing nakirah. The identified functions are ta‘mīm and takhṣīṣ. These findings indicate that the mubtada’ nakirah in Awa’iq Ath-Thalab is predominantly used to convey general meanings, advice, and motivation. This study contributes to Arabic syntactic studies by applying the theory of musawwighāt al-mubtada’ bi an-nakirah to the analysis of an Islamic classical text.